21-hydroxylase deficiency families with HLA identical affected and unaffected sibs. Issue 1 (January 1989) - Sinnott, P J; Dyer, P A; Price, D A; Harris, R; Strachan, T
Abstract : During our investigations of polymorphisms at, and in the immediate chromosomal vicinity of, the 21-hydroxylase locus in families with 21-hydroxylase deficiency, three families were found to show marked discordance in clinical features of HLA identical subjects. In one family, there is discordance between a boy with the simple virilising form of 21-hydroxylase deficiency and his two younger sisters, who are both HLA identical to their brother, but who have additional salt wasting features. In the other two families, one subject is severely affected and has very high 17-hydroxyprogesterone levels, but has an HLA identical sib who is asymptomatic and shows only slightly raised 17-hydroxyprogesterone levels. In all cases, HLA identity, as indicated by protein polymorphism studies (HLA-A, B, DR, C4A, C4B, and Bf typing), has been verified at the gene organisation level using 21-hydroxylase and complement C4 DNA probes. An HLA-Bw47 bearing haplotype in one of the latter families has not been transmitted to the affected child and appears to carry a normal 21-OHB allele and two genes which specify C4A allotypes.